Surgical Decompression of High-Grade Spinal Cord Compression from Hormone Refractory Metastatic Prostate Cancer. Issue 5 (24th May 2017) - Chohan, Muhammad Omar; Kahn, Sweena; Cederquist, Gustav; Reiner, Anne S; Schwab, Joseph; Laufer, Ilya; Bilsky, Mark
Abstract: BACKGROUND: Spine and nonspine skeletal metastases occur in more than 80% of patients with prostate cancer. OBJECTIVE: To examine the characteristics of the patient population undergoing surgery for the treatment of prostate cancer metastatic to the spine. METHODS: A retrospective chart review was performed on all patients treated at our institution from June 1993 to August 2014 for surgical management of metastatic spine disease from prostate cancer. RESULTS: During the study period, 139 patients with 157 surgical lesions underwent surgery for metastatic spine disease. Decompression for high-grade epidural spinal cord compression was required for 126 patients with 143 lesions. Preoperatively, 69% had a motor deficit and 21% were nonambulatory, with 32% due to motor weakness. At surgery, 87% of patients had hormone-refractory prostate cancer (HRPC) and 61% failed prior radiation. Median overall survival for HRPC patients was 6.6 mo (95% confidence interval [CI]: 5.6-8.6) while the median overall survival for hormone-sensitive patients was 16.3 mo (95% CI: 4.0-26.6). CONCLUSION: The majority of patients undergoing surgery for prostate cancer metastases to the spine were refractory to hormone therapy, indicating that patients with hormone-sensitive prostate cancer are unlikely to develop symptomatic spinal cord compression or spinal instability. A significant number of HRPC patients presented with neurological deficits attributable to spinal cord compression. Vigilant monitoring for the development of signs and symptoms of epidural spinal cord compression and spinal instability in hormone-refractory patients is recommended. Surgical decision making may be affected by the much shorter postoperative survival for HRPC patients as compared to patients with hormone-sensitive cancer.